Dystopia - Radwan, Amjad; Hazeem, Iyad; Halabi, Haytham (My University, 2017)
DYSOPIA is a virtual reality game that designed for personal computers, and it considered as adventure and fantasy game that the player uses first person shooter system, DYSOPIAhas a features that’s make it a strong game as Virtual reality support , Re-playable and Difficulty based on player experience ,DYSOPIAtakes consider of the performance and price ,it has a a lot of algorithms that’s make it stronger more and more ,our future work is to make it multiplayer and add more puzzles , weapons and levels .